Characterization of the wheat production in irrigated lands in Egypt - Devkota Wasti, Mina Kumari (2023)
In Egypt, wheat (Triticum aestivum) plays a pivotal role in the country’s agricultural and economic landscape. It is the major component of the national diet and an essential contributor to food security. Its cultivation in the country has a rich history dating back to ancient times. The Nile Delta has always been an ideal location for wheat cultivation. Historically, Egypt was known as the “Breadbasket of the Roman Empire”, highlighting its crucial role in sustaining its population and neighbouring regions. In the country, compared to all crops, it is grown in the largest area (1.33 million ha) and the country produces 9.1 million tons of wheat (average productivity of 6.81 t ha-1) (Source: Economic Affairs Sector, Ministry of Agriculture and Land Reclamation, 2023). Compared to all crops, its cultivation area is increasing in the country. However, it is meeting 50% of the demand from the international market to fill the gap between production and consumption (5.86 million t, one of the top 10th largest importers), where the import value of wheat and wheat products was 2.49 billion USD in 2021 (FAOSTAT, 2023).